(untitled) (Baltic Journal of Sport and Health Sciences, 2013)
Research background and hypothesis. In recent years, the phenomenon of stress and burnout among physical education teachers has been evidenced by researchers from many countries. It should be noted that all those studies about work difficulties of physical education teachers are individual. However, despite a large number of studies conducted and the progress made in this area, a universally accepted survey identifying five most important difficulties in physical education teachers’ work usually defined in contemporary studies still does not exist. This is mainly because there is still no consensus either on the decisive factors causing those difficulties for physical education teachers or what the central symptoms actually are. Research aim was (a) to review and (b) to identify five most important difficulties in physical education teachers’ work usually defined in contemporary studies. Research methods. This review examines research literature concerning the causes of stress and burnout of physical education teachers from the year 1999 to 2009 applying computer-aided literature search. The keywords used for the electronic search were “stress” and “burnout” or “job satisfaction” and “physical education teacher”. The main method of our research was logical deductive research literature analysis. Discussion and conclusions. Research literature review allowed identifying physical education teachers’ work difficulties (we found 24 of them). We established that the five most important difficulties in physical education teachers’ work usually defined in contemporary studies were as follows: low status of physical education; limited equipment, facilities and supplies; lack of time; large class sizes and excessive daily workloads. Keywords: burnout, job satisfaction, physical education teacher, stress.